Impact of Scalp Acupuncture Needling at the Vasomotor Area on Blood Pressure and Heart Rate Variability in Patients with Hypertension: A Randomized Controlled Study - C. Krithika; A. Mooventhan; S. Iswarya; L. Nivethitha; N. Mangaiarkarasi (Journal of Acupuncture Research, 2024)
Background: Increased blood pressure (BP) is a major health concern. Needling at the vasomotor area of the scalp helps in the management of hypertension. However, the impact of needling at the vasomotor area in hypertension still unclear. Thus, the present study aimed to investigate the impact of scalp acupuncture needling at the vasomotor area on BP and heart rate variability (HRV) in hypertension. Methods: Eighty participants with hypertension were randomly divided into the acupuncture (n = 40) and control (n = 40) groups. The acupuncture group received only one session of scalp acupuncture at the vasomotor area for 20 minutes, whereas the control group did not receive any intervention and was asked to rest in the sitting position for the same time duration. Pre- and postintervention assessments were performed. Results: Results showed a significant reduction in systolic BP, diastolic BP, mean arterial pressure, and HR and a significant increase in the interval between the two R-waves (RR-interval), standard deviation of RR-intervals, number of interval differences of successive NN intervals of > 50 ms (NN50), and proportion derived by dividing NN50 by the total number of NN intervals in the acupuncture group. However, a significant reduction in SBP, DBP, pulse rate, and MAP with no significant changes in HRV parameters were found in the control group. Conclusion: Twenty minutes of scalp needling at the vasomotor area reduced the participants’ BP and HR by increasing the HRV toward the parasympathetic activity. However, further studies are recommended to validate our study results.